Sexual Orientation, Peer Influence, Body Dissatisfaction, and Eudaimonic Well-Being in Italian Men - Matera, Camilla; Nerini, Amanda; Stefanile, Cristina (Frontiers in Psychology, 2019)
Having a lean and athletic physique is increasingly important for Italian men. The purpose of this cross-sectional study was to analyse the relationship between men’s dissatisfaction with muscularity and well-being, conceptualized in terms of the realization of one’s true potential and the experience of purpose or meaning in life (i.e., eudaimonic well-being), considering also the role of sexual orientation and peer influence. Participants (385 Italian men with a mean age of 28.61 years, SD = 9.65) completed a questionnaire assessing the variables of interest. Path analysis indicated that sexual orientation was linked to eudaimonic well-being via muscularity dissatisfaction. Teasing about muscularity predicted men’s eudaimonic well-being both directly and via muscularity dissatisfaction. Peer attributions and appearance conversations predicted well-being through the mediation of athletic internalisation and body dissatisfaction. Peer attributions, but not appearance conversations, were also directly linked to well-being. To improve broad aspects of men’s well-being, prevention and treatment programs should be directed to increase men’s ability to resist different forms of pressure, including that of their peers. These kinds of programs could be especially useful for gay men, who are more likely to experience body dissatisfaction and, in turn, poor psychological functioning.